Can different Catphan phantoms be used in a multi-centre audit of radiotherapy CT image quality?. (October 2020) - Davis, Anne T.; Palmer, Antony L.; Nisbet, Andrew
Highlights: Catphan phantoms of the same model have good consistency. Inter-phantom variability is much better than specification range suggests. Catphan 604 model have higher measured contrast than 504 model phantoms. Abstract: Purpose: To determine the variation between Catphan image quality CT phantoms, specifically for use in a future multi-centre image quality audit. Method: 14 Catphan phantoms (models 503, 504 and 604) were scanned on a Canon Aquilion Prime CT scanner using a single scan protocol. Measurements were made of noise in the uniformity section, visibility of low contrast targets and contrast, x-ray attenuation and CT number for 5 materials in the sensitometry section. Scans were also acquired using one phantom and varying reconstruction field of view, image slice thickness, effective tube-current-time product and iterative reconstruction settings to determine how the degree of inter-phantom variability compared with the magnitude of changes from scan parameter alteration. Results: Across all phantoms the mean CT value in the uniformity section was 7.0 (SD 0.9) range: 4.9–8.1 HU. For the different materials the CT numbers were air: −1004 ± 5, Polymethylpentene: −190 ± 2, Polystyrene: −42 ± 2, Delrin: 321 ± 5 and Teflon: 898 ± 8 HU. Consistency of low contrast targets through visual scoring was good. Measured contrast was lower ( p < 0.001) with more variability for 504 versus 604 models. All phantoms produced identical tube current settings with x-ray tube current modulation, indicating no x-ray attenuation differences. The degree of change in image quality metrics between phantoms was small compared with results when scan parameters were varied. Conclusion: Catphan phantoms model 604 showed minimal differences and will be used for multi-centre inter-comparison work, with the consistency between phantoms appropriate for measuring possible variations in image quality.